Solvent-assisted excited state proton transfer and photoacidity of 2-hydroxypyridine. A nonadiabatic dynamics study. Issue 3 (11th February 2019) - Hilal, Rifaat; Aziz, Saadullah G.
ABSTRACT: Reactions involving proton transfer, especially those taking place in excited states (ESPT), received considerable attention. These reactions underlie many biological and biochemical processes that are vital to life. DNA mutations excited state funnelling and transport phenomena are just examples. Among many molecules undergoing this type of photoreactions, phenols show a unique property, the so-called photoacidity. In the present communication, solvent (methanol and ammonia) assisted excited state proton transfer and photo acidity of 2-hydroxypyridine (2HP) are investigated at the DFT M06-2X / def2pvv level of theory. Excited states of 2HP and its complexes with methanol and ammonia were examined at two levels. First, sampling a Wigner distribution of 300 points, the photoabsorption spectra were simulated within the nuclear ensemble approximation. Second, simulation of the dynamics of the excited states with the surface hopping method. Several separate spectral windows with three hundred trajectories each, were considered. Lifetime of excited states and photochemical channels observed were discussed.